The use of bidirectional transcription footprinting to detect platinum-DNA crosslinks by acridine-tethered platinum diamine complexes and cisplatin. - Cullinane, C (1993)
Bidirectional transcription footprinting has been used to probe the platination of DNA by cisplatin, and to examine the modulation of these interactions by (a) cyclisation of the non-reactive amino group by either ethyl or propyl groups, and (b) the further addition of a pendant intercalator (9-amino acridine) linked by either phenylethyl or phenylpentyl groups. Intrastrand crosslinking was detected for all derivatives at all 5'-GG and 5'-AG sequences on the template strand, but the same sites did not result in transcriptional blockages when on the non-template strand. There was little effect of cyclysation of the amino groups, but the further addition of an intercalator resulted in three responses: a time-dependent increase of the blocked transcript by one and three nucleotides; a reduction of the sequence selectivity of platination; a decrease of apparent interstrand crosslinking for these derivatives with a pendant intercalator tethered to the amino moiety of cisplatin.